A New Method for Fluid Identification of Low-Contrast Oil Layers in the Western Margin of Ordos Basin - ZHOU Yan; LUO Shaocheng; MU Yu; LEI Linlin; CHEN Lu; LIN Weichuan (Cejing jishu)
With the deepening of exploration and development, oilfield exploration and development objects are increasingly complex, and the low contrast characteristics of oil and water layers are more prominent. Influenced by various factors such as sedimentary microfacies, source-reservoir configuration, and injection degree, low-contrast oil reservoirs exhibit strong concealment, complex oil-water relationships, and a high difficulty in log identification and evaluation, resulting in a low interpretational matching rate. Therefore, there is an urgent need to establish effective technology for identifying fluid in low-contrast oil layers to enhance log interpretation accuracy. This article takes the example of the Chang 8 reservoir in the western part of the Huanjiang oilfield on the western margin of the Ordos basin. The research begins by studying lithology, physical properties, water properties, oil content, and other aspects, conducting an in-depth analysis of the genesis mechanism of low-contrast oil layers in the study area. The study suggests that differences in formation water salinity, high bound water saturation, and low reservoir injection degree are important factors leading to the appearance of low-resistivity and low-contrast characteristics in the Chang8 oil layer in the western part of the Huanjiang oilfield. Based on this analysis, a fluid-sensitive factor identification method is specifically established. Innovatively, from the perspective of the energy composition of logging signals, a multi-scale wavelet energy spectrum fluid identification technology is developed by constructing fluid-sensitive logging curves. To address the low injection degree of the reservoir in the study area, an evaluation method for subdividing oil and water layers based on capillary imbibition experiments is innovatively developed. The above three methods have effectively improved the ability to identify the fluid properties of low-contrast reservoir in the study area, and have a significant application effect in the identification of low-contrast reservoir.